2017
DOI: 10.18203/2394-6040.ijcmph20170284
|View full text |Cite
|
Sign up to set email alerts
|

The knowledge of osteoporosis risk factors and preventive practices among women of reproductive age in the state of Qatar: a cross-sectional survey

Abstract: INTRODUCTIONOsteoporosis knowledge is one of several factors that are associated with osteoporosis preventive behavior. Moreover, the educational level of individuals has the potential to change the perception of health and illness to a much better level. Thus, highly educated people usually seek knowledge and have an opportunity to learn about health preventive behavior more than those with a lower educational level.1 Similarly, elderly women who, during ABSTRACTBackground: Osteoporosis is a global health pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…In the present study, a moderate level of knowledge regarding osteoporosis was indicated among the subjects. This observation was in line with previous studies on knowledge regarding osteoporosis among Malaysian adult populations [23,24]; adult women (aged >40 years old) in Alexandria, Egypt [43], and Arabian women (aged 20 to 44 years old) in Qatar [44]. The study participants were aware of the general and prevention knowledge regarding osteoporosis, that is, it might increase fracture risk, is a treatable disease, and is associated with menopause.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, a moderate level of knowledge regarding osteoporosis was indicated among the subjects. This observation was in line with previous studies on knowledge regarding osteoporosis among Malaysian adult populations [23,24]; adult women (aged >40 years old) in Alexandria, Egypt [43], and Arabian women (aged 20 to 44 years old) in Qatar [44]. The study participants were aware of the general and prevention knowledge regarding osteoporosis, that is, it might increase fracture risk, is a treatable disease, and is associated with menopause.…”
Section: Discussionsupporting
confidence: 88%
“…This corresponds to our findings, as age increased, there was some advancement of knowledge in relation to diet for chronic diseases. 5 Studies done by Hasan et al and Kim, Lee, Shin, Park, found out that, there was signifivant association between schoolasti education and awareness of diet in chronic diseases like osteoporosis. They found out significant association in educational status and awareness for diet in chronic health conditions.…”
Section: Discussionmentioning
confidence: 97%
“…In Egypt; osteopenia prevalence (53.9%) and osteoporosis prevalence (28.4%) [22]. Misunderstanding about osteoporosis and the absence of preventive activity among women are as yet not change, making primary avoidance at an early age the best mediation [11]. As a result of hormonal changes or deficiency of calcium or vitamin, bones become weak and fragile due to loss of tissue.…”
Section: Discussionmentioning
confidence: 99%